(3EOGQI GdefGRYGJ GdVQjHjI aj QHW hJMUjd GdVQGFH (B/s - (3CHh cQT, TQja eUHGMs ((3YeGf(B: s (3OGQ GdefGgL ddfTQ(B, s, 2004)
(3LGA gPG GdcJGH aj YTQI aUhd MjK JYQV dehVhY GdEOGQI GdVQjHjI hbOe eaghegG hCgejJgG hYfGUQgG hSeGJ GdEOGQI GdVQjHjI GdLjOI ceG JfGhd GdJYOjdGJ GdJj WQGAJ Ydi bhGfjf VQjHI GdONd ceG bOe eMJhi TGed dehVhY GdWYf aj VQjHI GdONd aj GdJTQjY GdVQjHj CVGaI Gdi JbOje MGdGJ YedjI aj GdbVGA GdVQjHj daGFOI GdOGQSjf hGdHGMKjf hdJbQjH GdehVhY ef GdfGMjI GdYedjI(B. (3fPcQ JSdSd GdaUhd Ydi GdfMh GdJGdj GdGOGQI GdVQjHjI ,JdNjU dbGfhf VQjHI GdONd GdGQOfj,JYOjdGJ bGfhf VQjHI GdONd , GdWYf aj GdJTQjY GdVQjHj GdebGQf, GdWYf aj QHW GdVQGFH ZjQ GdeHGTQI , GdeMGce aj bGfhf VQjHI GdONd, GKQ GfJVGaI GdGbUi Ydi GdMUjdI GdVQjHjI ddSdWI GdadSWjfjI , WQb GdWYfj aj VQjHI GdONd aj GdJTQjY GdadSWjfj(B.(3GdeUQj(B.(3GdYQGbj(B.(3GdShQj (B.(3GdGQOfj, WQb JbOjQ VQjHI GdONd aj GdJTQjY GdVQjHj GdebGQf, MGdGJ YedjI aj GdbVGA GdVQjHjs
(3HjHdjhZQGajG U(B.293s
Keywords: (3GdVQGFHs; (3GdVQGFH(B- (3LeY s; (3GdVQGFH(B- (3NUheGJ s